COMMERCIALIZATION OF INTELLECTUAL DEVELOPMENT OF KAZAKHSTAN - Azatbek Tolkyn; Bekenova Lidiya; Baimukasheva Zhanymgul; Velesco Serge (Scientific Journal of Pedagogy and Economics, 2019)
The article is devoted to the legal and organizational mechanisms for ensuring the commercialization of intellectual property in the Republic of Kazakhstan. Authors analyzed the factors, infrastructure and institutions of commercialization, assessed the activities of subjects of commercialization. The activity of enterprises in obtaining security documents for intellectual property was analyzed. The types of intellectual property that occupy the greatest share in the structure of issued security documents are identified. An assessment of the licensing activities dynamics related to innovation is given. The analysis of innovative activity of enterprises in Kazakhstan was carried out and the main trends of its dynamics were identified. Authors proposed measures to stimulate the commercialization of the intellectual development of Kazakhstan based on the studied foreign experience. The authors suggest that the greatest potential for stimulating the commercialization of intellectual property results is the development of venture capital financing. The most effective way is the adoption and implementation of the state program for the development of venture capital investment, because the state will be able to act as a guarantor of reliability. In addition, the authors proposed the use of venture financing methods tested in international practice, in which investments are made in stages to reduce risks.